2021
DOI: 10.1108/ijchm-08-2020-0822
|View full text |Cite
|
Sign up to set email alerts
|

The cleanliness of restaurants: ATP tests (reality) vs consumers’ perception

Abstract: Purpose This study aims to empirically assess restaurant surfaces’ cleanliness and compare them to customers’ perceptions about the cleanliness of surfaces when dining in a restaurant. Design/methodology/approach This study used two methods to collect data. The first was a survey method to gauge customers’ perceptions and an empirical test to measure cleanliness using an adenosine triphosphate (ATP) meter. Two data sets were collected to compare customers’ perceptions and actual cleanliness measurements. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…Previous research has shown that sanitation in a restaurant environment could impact customers' positive or negative emotions (Park et al, 2016). Similarly, researchers (Kim et al, 2021a;Naumov et al, 2021) demonstrated that trust in the cleanliness of restaurants and sanitation of accommodations is an important variable predicting customers' intentions to visit. Recovering the hotel industry from large-scale public health crises such as SARS or pandemic, researchers (Jiang and Wen, 2020;Kim et al, 2005;Choi, 2019) widely discussed the importance of hygiene and cleanliness for hotel operations to meet guests' high expectations of their safety while traveling.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that sanitation in a restaurant environment could impact customers' positive or negative emotions (Park et al, 2016). Similarly, researchers (Kim et al, 2021a;Naumov et al, 2021) demonstrated that trust in the cleanliness of restaurants and sanitation of accommodations is an important variable predicting customers' intentions to visit. Recovering the hotel industry from large-scale public health crises such as SARS or pandemic, researchers (Jiang and Wen, 2020;Kim et al, 2005;Choi, 2019) widely discussed the importance of hygiene and cleanliness for hotel operations to meet guests' high expectations of their safety while traveling.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic specifically has forced many businesses to close for some period of time and most countries in the world have closed their borders at some points during the past year. Among all sectors of the economy, the restaurant industry, a highly social and interactive service business, has been one of the most severely affected financially and economically (Kim et al, 2021a(Kim et al, , 2021b. It is expected to have an unprecedented decline until a new treatment or vaccine for COVID-19 is widely available that can resolve the original strain and focus on the new variants recently introduced to the world in 2021.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, there was a need for improved cleaning and handling techniques and the importance of proper training for the employees. This is important to ensure the cleanliness of food stall facilities (Kim et al, 2021;Truong et al, 2017).…”
Section: A)mentioning
confidence: 99%
“…The COVID‐19 pandemic has created an environment of rapid adaptations and the adoption of new practices (Pillai et al, 2021). Service industry practitioners have adapted their servicescape (Bitner, 1992) in order to meet the hygiene expectations in service areas (Kim et al, 2021; Taylor, 2020). For instance, restaurants have practiced sanitizing common touchpoint areas, ranging from table surfaces to door handles, in their physical servicescape settings.…”
Section: Introductionmentioning
confidence: 99%